Artificial Intelligence: The Biggest Threat to Democracy Today? - Nie, Michelle (Proceedings of the AAAI Symposium Series, 2024)
The impact of generative artificial intelligence (GenAI) on increasing misinformation is well-understood. But there remain questions on how GenAI impacts the well-being of individuals and societies at large. This paper tackles this question from a political science standpoint and considers the impact on democracy, which is linked to individual and social well-being. It examines aspects of AI systems, including GenAI systems, that threaten to undermine democracy the most, such as misinformation. This paper also clarifies the nature of these threats to democracy, makes the connection to epistemic agency and political trust, and outlines potential outcomes to society and political institutions, including accelerating the rise of populism, the enhancement of authoritarian governments, and the threat of rule by algorithms.